The G209A mutation in the alpha-synuclein gene in Brazilian families with Parkinson's disease Mutação G209A no gene da alfa-sinucleína em famílias brasileiras com doença de Parkinson - Hélio A.G. Teive; Salmo Raskin; Fábio M. Iwamoto; Francisco M.B. Germiniani; Maria H.H. Baran; Lineu C. Werneck; Nasser Allan; Elizabeth Quagliato; Elisabeth Leroy; Susan E. Ide; Mihael H. Polymeropoulos (Arquivos de Neuro-Psiquiatria)
A missense G209A mutation of the alpha-synuclein gene was recently described in a large Contursi kindred with Parkinson's disease (PD). The objective of this study is to determine if the mutation G209A of the alpha-synuclein gene was present in 10 Brazilian families with PD. PD patients were recruited from movement disorders clinics of Brazil. A family history with two or more affected in relatives was the inclusion criterion for this study. The alpha-synuclein G209A mutation assay was made using polymerase chain reaction and the restriction enzyme Tsp45I. Ten patients from 10 unrelated families were studied. The mean age of PD onset was 42.7 years old. We did not find the G209A mutation in our 10 families with PD. Our results suggest that alpha-synuclein mutation G209A is uncommon in Brazilian PD families. Recentemente foi detectada mutação missense G209A no gene da alfa-sinucleína em uma grande família com doença de Parkinson (DP) de Contursi, Itália. Este estudo tem o objetivo de determinar se a mutação G209A está presente em 10 famílias brasileiras com DP. Pacientes com DP foram recrutados em clínicas de distúrbio do movimento no Brasil. O critério de inclusão no estudo foi à presença de dois ou mais familiares acometidos pela DP. A mutação G209A do gene da alfa-sinucleína foi pesquisada usando a técnica de reação em cadeia de polimerase e a enzima de restrição Tsp45I. Foram estudados 10 pacientes de famílias não-relacionadas. A idade média do início dos sintomas da DP foi 42,7 anos. Não encontramos a mutação estudada neste grupo de pacientes. Nossos resultados sugerem que a mutação G209A é incomum em famílias brasileiras com DP.